Sayyid Quṭb’s critique of fiqh - Ushama, Thameem (Intellectual Discourse, 2014)
Sayyid Quṭb’s views on fiqh (jurisprudence) have been the subject of significant critique. This paper seeks to understand the bases of such criticisms through a qualitative content analysis of his exegesis and other writings. We begin with a brief survey of the views of scholars who have spoken in favour of and against him, followed by a brief biographic profile of Quṭb. This paper focuses on Quṭb’s critique of three key issues. First, the terms “Fiqh al-Awrāq” (jurisprudence of papers) and “Fiqh al-Ḥarakah” (dynamic jurisprudence) as employed during his discourse on fiqh are analysed. Second, his interpretation of the concept of “Dār al-Islām” (Land of Islam) and “Dār al-Ḥarb” (Hostile Land) that led to criticisms by jurists are analysed through a comparison with the views of other jurists. Third, his discourse on the application of the concept of al-marḥaliyyah (stages) in jihād, that caused misunderstandings among jurists, is analysed in the context of a response to the need for developing dynamic jurisprudence for contemporary communities. The study endeavours to dispel ambiguities and present an objective account of Quṭb’s discourse on fiqh.